If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -19 + -5x + 7 + -3x + -1 = 4x + -5 + 6x + 7 + -2x + -1 Reorder the terms: -19 + 7 + -1 + 3x + -5x + -3x = 4x + -5 + 6x + 7 + -2x + -1 Combine like terms: -19 + 7 = -12 -12 + -1 + 3x + -5x + -3x = 4x + -5 + 6x + 7 + -2x + -1 Combine like terms: -12 + -1 = -13 -13 + 3x + -5x + -3x = 4x + -5 + 6x + 7 + -2x + -1 Combine like terms: 3x + -5x = -2x -13 + -2x + -3x = 4x + -5 + 6x + 7 + -2x + -1 Combine like terms: -2x + -3x = -5x -13 + -5x = 4x + -5 + 6x + 7 + -2x + -1 Reorder the terms: -13 + -5x = -5 + 7 + -1 + 4x + 6x + -2x Combine like terms: -5 + 7 = 2 -13 + -5x = 2 + -1 + 4x + 6x + -2x Combine like terms: 2 + -1 = 1 -13 + -5x = 1 + 4x + 6x + -2x Combine like terms: 4x + 6x = 10x -13 + -5x = 1 + 10x + -2x Combine like terms: 10x + -2x = 8x -13 + -5x = 1 + 8x Solving -13 + -5x = 1 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -13 + -5x + -8x = 1 + 8x + -8x Combine like terms: -5x + -8x = -13x -13 + -13x = 1 + 8x + -8x Combine like terms: 8x + -8x = 0 -13 + -13x = 1 + 0 -13 + -13x = 1 Add '13' to each side of the equation. -13 + 13 + -13x = 1 + 13 Combine like terms: -13 + 13 = 0 0 + -13x = 1 + 13 -13x = 1 + 13 Combine like terms: 1 + 13 = 14 -13x = 14 Divide each side by '-13'. x = -1.076923077 Simplifying x = -1.076923077
| 16x^3+12x^2-24x+7=0 | | tan(-x)=-tan(x) | | 780000=x/(x/0.4) | | 2y-3x=30 | | 4p-05=5p-05 | | (13X)(7X)=50 | | 6x-1=7y | | Z^2+4z-i+4=0 | | 4(3x)+x=22+x | | 9x=3-4x | | 5:a=10 | | 5:=10 | | 5:x=10 | | 0=0.75+4.9x | | -238x=112 | | 3x-15-4x=-9+x-13 | | cos(2x+20)=0.5 | | 3x-15-4=-9+x-13 | | Y=y^3cosx | | 3x-4=12-7x | | x^2-y^2+4*x+6*y-13=0 | | 2x-22-9x=42+11x-100 | | 1.00+x=1.10 | | x^4-4x^3+7x^2-4x=0 | | p(t)=-16t^2+20+50 | | A(2a+1)(3a-2)=0 | | (25-43)/2-7 | | 7=(11*2)+p | | (x^2+x-1)(x^2+3x+1)=55 | | 3x+9-2x+5=6x-4+7 | | 5x-4=11-5 | | 3x+19=7x-53 |